Primary pupils' creative writing: enacting identities in a Community of Writers. (19th May 2017) - Dobson, Tom; Stephenson, Lisa
Abstract: This paper focuses on a Community of Writers creative writing project where 25 primary school pupils from lower socio‐economic backgrounds took part in creative writing workshops over a 2‐week period at a higher education institution. Using practitioner enquiry and discourse analysis, this paper views identity as participation in 'figured worlds' and highlights the relationship between the children's creative writing outputs and their shifting identities (Holland et al., 1998 ). A case is made that children's authentic creative writing can be nurtured by a community that promotes intertextuality and 'hybridity' (Bakhtin, 1981 ) as well as balancing pedagogical 'structure' and 'freedom' (Davies et al., 2012 ) in order to provide textual space for writers to enact different identities. At a time when the global figuring power of performativity (Ball, 2003 ) actively restricts the ways in which teachers and children interact, this paper also presents an informed argument for the value of school–university research partnerships.